DECISION SUPPORT SYSTEM SELECTING CRYPTOCURRENCY EXCHANGE USING AHP METHOD - Dewi Monica; Wahyu Tisno Atmojo (Jurnal Teknik Informatika (Jutif), 2023)
Cryptocurrency is a digital currency that functions as a standard currency and can be traded virtually without service fee and have a reliable institution. Investors and traders are interested in buying or acquiring cryptocurrencies and expect to make a profit when selling them. Apart from mining, cryptocurrencies can obtain by buying through cryptocurrency exchanges. The cryptocurrency exchange is helpful as an intermediary for buying and selling crypto assets. There are many types of cryptocurrency exchanges circulating, and it makes users have to select carefully the exchanger they will use. Based on this problem, a decision support system is needed to facilitate the decision-making. The method used in this research is the Analytical Hierarchy Process (AHP). This method is selected because it helps multi-criteria decision-making, solves complex problems into small forms, and receives input from human understanding by defining problems, making hierarchies, conducting comparative assessments, determining priorities, and calculating consistency values. The final result of this research using the AHP method can be seen that Binance is the most recommended cryptocurrency exchange to be used for investing or trading because it earns a percentage of 35.34%, followed by FTX at 28.35%, Huobi Global at 18.05%, Gate.io at 6.96%, KuCoin at 5.76%, and Indodax 5.55%. The results of this calculation are obtained by calculating the priority criteria and alternatives.